Effects of 20 % versus 40% velocity loss resistance training programs on neuromuscular adaptations of lower and upper body in young men and women - Rissanen, Joonas (2019)
Introduction: In recent years the velocity-based resistance training (VBRT) approach has gained popularity in sports coaching and scientific research. VBRT is classified as resistance training in which movement velocity is used as a depended variable in quantifying the training load (intensity, volume, e.g.). An important application of VBRT is quantifying the optimal number of repetitions per set to target to specific training adaptations by using the velocity loss within the set as a determinant. The purpose of this study was to compare neuromuscular effects of two different, 20 and 40 %, within set velocity loss resistance programs (VL20 and VL40) in lower and upper body in young men and women. Methods: The study included a one-week control period and thereafter an 8-week training intervention consisting 15 training sessions. Measurements were made in four testing sessions: Control, Pre, Mid and Post. 24 healthy young men (aged 26.4 ± 3.9 years) and 25 women (aged 25.5 ± 3.8 years) were assigned to 4 different groups: VL20M = 20 % velocity loss men (n=12), VL40M = 40 % velocity loss men (n=12), VL20W = 20 % velocity loss women (n=13) and VL40W = 40 % velocity loss women (n=12). The training program consisted two exercises: Smith machine full back squat (BS) and Smith machine bench press (BP). During the training program, all the repetitions were performed with the maximal initial velocity in every training session and the training intensity and the number of repetitions per each set were determined by using the velocity-based approach. Both VL20 groups continued performing their exercise sets until they reached the within-set mean propulsive velocity (MPV) loss of 20 % and both VL40 until the MPV loss of 40 %. The following neuromuscular measurements were performed: 1RMs in BS and BP, mean MPVs against high and low submaximal loads in BS and BP, countermovement jump (CMJ), squat jump (SJ), maximal isometric leg press force (ILP Fmax), maximal isometric bench press force (IBP Fmax), rate of force development (RFD) in ILP, average force during 0-100 ms (F100ms) in ILP, integrated electromyography (IEMG) during 500-1500 ms in ILP and during the concentric phase in CMJ as well as vastus lateralis (VL) cross-sectional area (CSA). Results: Significant (p<0.05) increases in BS and BP 1RMs (mean 7–10 %) were observed in both groups in men. VL20M and VL40M also showed significant increases (p<0.05) in VL CSA at Post (mean 15–20